Acute pancreatitis and biliary obstruction from metastatic lymph node compression during [177Lu] Lu-PSMA-617 therapy: a case report - Belge Bilgin, Gokce; Navin, Patrick J.; Johnson, Derek R.; Sartor, Oliver; Kendi, Ayse Tuba (Frontiers in Oncology, 2024)
Radioligand therapies such as [177Lu] Lu-PSMA-617 have gained significant momentum in cancer treatment after clinical trials and multicenter studies demonstrated their safety and efficacy. As these innovative treatments become more widespread, rare and unique clinical manifestations are expected to be observed. In this report, we describe a case with metastatic castration-resistant prostate cancer (mCRPC) and peripancreatic lymph node metastases who developed acute pancreatitis following [177Lu] Lu-PSMA-617 therapy.